Inflammatory mediators and the RAGE pathway in placental tissues of pregnancies complicated by severe preeclampsia - Chandra, Neelima; Kimble, Thomas D.; Heim, Kathleen R.; Anderson, Sharon M.; Wong, Andrew P.; Thurman, Andrea R.; Doncel, Gustavo F. (Frontiers in Reproductive Health, 2025)
IntroductionPreeclampsia (PE) is a complex multisystem disorder of pregnancy associated with abnormal placentation, vascular anomalies, and systemic inflammation and hypertension. Previous research assessing inflammatory triggers of the condition used plasma, amniotic fluid, or explant samples. Studies using placental tissue from either vaginal or cesarean deliveries are confined to semiquantitative analysis using subjective scoring methods and generally involve a small sample size.MethodsIn this study, we have quantified the expression of inflammatory mediators by immunohistochemical image analysis of archived placental tissues obtained from cesarean delivery of preeclamptic, chorioamnionitic, and normal pregnancies.ResultsAmong the inflammatory mediators, we found a significant elevation in the expression of receptors of advanced glycation end products (RAGE) and two of its damage-associated molecular pattern proteins (DAMPs) and ligands, the high mobility group box protein HMGB1 and the calcium binding protein S100, in preeclamptic tissues as compared to normal placentas. In addition, we observed a significant increase in the master pro-inflammatory transcription factor, nuclear factor kappa B p65 subunit (NFκB), as well as non-significant increases in cyclooxygenase 2 (COX-2) and interleukin 8 (IL-8) in the PE group.ConclusionThis study provides insight into the relationship of tissue inflammatory mediators with severe preeclampsia and the RAGE associated signaling complex, suggesting a pathogenic role for this pathway which has clinical implications for the understanding, diagnosis, and potential novel therapeutic approaches to the syndrome.